The impact of partial oil substitution and trace metal ions on the evolution of peroxidation products in thermally stressed culinary oils. (1st May 2022) - Ampem, Gilbert; Gresley, Adam Le; Grootveld, Martin; De Mars, Simon; Naughton, Declan P.
Highlights: Certain LOPs evolve faster than others and partial substitutions have different effects on the individual LOP concentrations that goes beyond just dilution. Partial substitutions of culinary oil potentially offer to be an effective chemical-free scientific technique in suppressing LOPs at 180℃. ICP-OES investigation of culinary oils revealed that the concentrations of trace metal ions did not influence the types and levels of LOPs in the studied culinary oils. Abstract: Suppressing toxic aldehydic lipid oxidation product (LOP) generation in culinary oils is now considered vital, since the deleterious effects arising from their ingestion are implicated in a wide range of disease conditions. Partial substitution involves the replenishment of thermally-stressed culinary oils with corresponding unheated ones. This technique was tested by employing 10%, 25%, 50%, and 75% (v/v) partial substitutions of coconut, olive, rapeseed, and sunflower oils at 180℃ for a 300 min continuous thermo-oxidation duration. Oil samples were analysed by proton nuclear magnetic resonance ( 1 H NMR) spectroscopy. Trace metal levels, including oxidation–reduction (redox)-active metal ions credited with enhancing cooking oil oxidation were also analysed using inductively coupled plasma-optical emission spectroscopy (ICP-OES). As expected, the degree of oil unsaturation, and the % partial substitutions significantly influenced their susceptibility to thermo-oxidation. In view of the very low polyunsaturated fatty acid (PUFA) and monounsaturated fatty acid (MUFA) contents of coconut oil, both the class and concentrations of evolved LOPs were found to be least affected by this partial substitution process. Aldehydic LOPs were greatly suppressed in partially-substituted rapeseed oil. The % suppression activity of LOPs evaluated for the partially substituted oils were generally high making partial oil substitutions an effective chemical-free method in suppressing LOPs at both industrial and commercial levels. In general, the % partial oil substitutions were directly related to the dilution effect observed for LOPs quantified in the oils. Furthermore, trace metal ion concentrations measured in the culinary oils did not influence the evolution of LOPs in the oils.